2020
DOI: 10.1186/s13765-020-00569-z
|View full text |Cite
|
Sign up to set email alerts
|

Removal of TPH, UCM, PAHs, and Alk-PAHs in oil-contaminated soil by thermal desorption

Abstract: Oil-contaminated soils from a former landfill and gas station site in Korea were treated by thermal desorption. The removal efficiencies of the different oil components such as total petroleum hydrocarbons (TPH), polyaromatic hydrocarbons (PAHs), unresolved complex mixtures (UCM), and alkylated PAHs (Alk-PAHs) by thermal desorption were determined. The effects of temperatures (200, 400, and 600 °C) and treatment times (15, 30, 45, and 60 min) on the thermal desorption efficiency were studied. The treatment eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…Another previous study reported 70% TPH removal from an oil-contaminated soil sample after treatment at 300 °C for 10 min [ 26 ]. In contrast to a previous study, as a result of controlling the moisture content in the pyrolysis method in the case of TPH when it was operated at 200 °C for 60 min, it was possible to confirm the high removal efficiency of 91.61% and 93.68% at the water content of 10% and 20%, respectively [ 25 ]. In addition, the residual amounts of TPH and UCM decreased significantly up to 200 °C, but it was confirmed that sharpness decreased when applied at a higher temperature.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…Another previous study reported 70% TPH removal from an oil-contaminated soil sample after treatment at 300 °C for 10 min [ 26 ]. In contrast to a previous study, as a result of controlling the moisture content in the pyrolysis method in the case of TPH when it was operated at 200 °C for 60 min, it was possible to confirm the high removal efficiency of 91.61% and 93.68% at the water content of 10% and 20%, respectively [ 25 ]. In addition, the residual amounts of TPH and UCM decreased significantly up to 200 °C, but it was confirmed that sharpness decreased when applied at a higher temperature.…”
Section: Resultscontrasting
confidence: 68%
“…As a result of pyrolysis at 600 °C for 60 min, the residual amount of TPH was not statistically significant as a result of the t-test, according to the difference in moisture content ( p -value = 0.001). In our previous study on the open system pyrolysis, the TPH removal rates of 74% and 76% were obtained after 30 min and 60 min treatments at 200 °C [ 25 ]. In this study, the closed system pyrolysis achieved higher TPH removal rates (i.e., 88% and 93% after 30 min and 60 min, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In the small-scale test, researchers mainly obtained thermal desorption effects under different experimental conditions. The effects of temperatures and treatment times on the thermal desorption efficiency were studied by the thermal desorption of oil-contaminated soils from a former landfill and gas station site in Korea . The study showed that the different components of oil in the oil-contaminated soils could be treated effectively in a relatively short time by thermal desorption.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of temperatures and treatment times on the thermal desorption efficiency were studied by the thermal desorption of oil-contaminated soils from a former landfill and gas station site in Korea. 9 The study showed that the different components of oil in the oilcontaminated soils could be treated effectively in a relatively short time by thermal desorption. Zhang influence of heating temperature and residence time on the disposal effect.…”
Section: Introductionmentioning
confidence: 99%
“…When released in surroundings, they portend great ecological and health concern. Choi et al, [4] reported that PAHs are one of the main elements of crude oil. Annually, large quantities of petroleum products are discharged into the soil and water bodies either accidentally or improperly due to mining, transportation, leakages from pipelines and blow outs.…”
Section: Introductionmentioning
confidence: 99%